If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -7) = -3x + -1(2 + -6x) Reorder the terms: 2(-7 + x) = -3x + -1(2 + -6x) (-7 * 2 + x * 2) = -3x + -1(2 + -6x) (-14 + 2x) = -3x + -1(2 + -6x) -14 + 2x = -3x + (2 * -1 + -6x * -1) -14 + 2x = -3x + (-2 + 6x) Reorder the terms: -14 + 2x = -2 + -3x + 6x Combine like terms: -3x + 6x = 3x -14 + 2x = -2 + 3x Solving -14 + 2x = -2 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -14 + 2x + -3x = -2 + 3x + -3x Combine like terms: 2x + -3x = -1x -14 + -1x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 -14 + -1x = -2 + 0 -14 + -1x = -2 Add '14' to each side of the equation. -14 + 14 + -1x = -2 + 14 Combine like terms: -14 + 14 = 0 0 + -1x = -2 + 14 -1x = -2 + 14 Combine like terms: -2 + 14 = 12 -1x = 12 Divide each side by '-1'. x = -12 Simplifying x = -12
| -6p-3=-12-5p | | (6-4)(8b^2-5b+6)= | | 13-[5+5y-3(y+3)]=-3(4y-7)-[8(y-1)-16y+18] | | 2(b+8)-9=18 | | 3=y-21 | | 8x-3=2x+33 | | 4x=4m | | (2x+y+1)(2x+y+1)= | | -5n=13-3+1n-2,2,4 | | -4+3x=-8(5+4x)+1 | | 5-7(k-5)=96 | | -2y+x=4 | | 4(p)+8(8-p)=44 | | -2y+9=21 | | 5([6-5x])=15x-35 | | a+(a+1)+(a+2)=36 | | 4x+1(x+2)=56-2x | | 2(4+2a)+10=a | | cx^2+3x+c-2=0forx | | -101=5(-7+2m)-6 | | -2/3x+4=3/5x-2 | | 6a+2b=b | | 2-6x=1-x | | x^3+6x^2+x-14=0 | | h/2=-2 | | 68.707+(-99.999)+32.592= | | w^2+5w-594=0 | | 15y-10+k=(ky-1)-y | | -5(-6n-8)-8n=150 | | 2(-8+v)=-16+6v | | 6-5x=20x-35 | | -3+y=25 |